International activity of sports universities: state and trends of development - Lubysheva, L.I.; Rosenko, S.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify current trends and determine the vector of development of the international activities of Russian universities of physical culture and sports. Methods and structure of the study. The analysis of the main parameters of international activity in Russian universities of physical culture and sports has been carried out. Results and conclusions. At present, the state of international activity of universities is one of the key indicators of their effective development. The vectors for the development of international activities of sports universities are: the development of exports of educational services of scientific projects; formation of a stable contingent of foreign students, integration of educational organizations of higher education into the international educational and scientific space; increase in income from the export of educational services and scientific products of universities; promotion of the "brand" of universities in the international educational and scientific space; internationalization of educational and scientific activities of universities; development of academic mobility; implementation of network educational programs, etc. The goal of implementing the strategy for the development of international activities is to increase the competitiveness of sports universities in the international space and strengthen their export potential.